Religious Diversity at School: Educating for New Pluralistic Contexts - Aslan, Ednan; Hermansen, Marcia K. (Wiener Beiträge zur Islamforschung, 2021)
With contributions by: Ednan Aslan, Maria Hermansen -- Almeda M. Wright -- Ina ter Avest -- Arniika Kuusisto, Liam Gearon, Saija Benjamin, Pia Koirikivi -- Manfred L. Pirner and Julia Bradtke -- Michael Ameen Kramer -- Cem Kara -- S. Hermisson, P. Gochyyev -- Şenol Yağdı -- Wolfgang Weirer -- Zsófia Windischö Martin Rothgangel -- Areti Demosthenous -- Henrik Simojoki -- Rositsa Atanasova -- Muhamed ALI -- Brylov Denis -- Holger Daun -- Genti Kruja -- Mehmet H. Tuna -- Farid Panjwani -- Leila Almazova -- Ali Yaman -- Sami Adwan.